Volumetric Modulated Arc Therapy for Spine Radiosurgery: Superior Treatment Planning and Delivery Compared to Static Beam Intensity Modulated Radiotherapy - Zach, Leor (Biomed Res Int, 2016)
Purpose. Spine stereotactic radiosurgery (SRS) delivers an accurate and efficient high radiation dose to vertebral metastases in 1–5 fractions. We aimed to compare volumetric modulated arc therapy (VMAT) to static beam intensity modulated radiotherapy (IMRT) for spine SRS. Methods and Materials. Ten spine lesions of previously treated SRS patients were planned retrospectively using both IMRT and VMAT with a prescribed dose of 16 Gy to 100% of the planning target volume (PTV). The plans were compared for conformity, homogeneity, treatment delivery time, and safety (spinal cord dose). Results. All evaluated parameters favored the VMAT plan over the IMRT plans. D (min) in the IMRT was significantly lower than in the VMAT plan (7.65 Gy/10.88 Gy, p < 0.001), the Dice Similarity Coefficient (DSC) was found to be significantly better for the VMAT plans compared to the IMRT plans (0.77/0.58, resp., p  value < 0.01), and an almost 50% reduction in the net treatment time was calculated for the VMAT compared to the IMRT plans (6.73 min/12.96 min, p < 0.001). Conclusions. In our report, VMAT provides better conformity, homogeneity, and safety profile. The shorter treatment time is a major advantage and not only provides convenience to the painful patient but also contributes to the precision of this high dose radiation therapy.